Analisis Manajemen Risiko pada UMKM Good Place Vapor - Dhafin Al-Rasyid Sastradireja; Ghulam Priyatna Yoniar; Elky Rimba Priatna; Aris Kurniawan; Alfiana Alfiana (Indo Publishing, 2026)
This research aims to analyze risk management implementation in GOOD PLACE VAPOR, an SME in Bandung Regency operating in the vapor product retail industry. Using a descriptive qualitative approach with SWOT analysis and risk matrix, this study identifies four main risk categories: market, operational, human resources, and legal risk. The findings indicate that hight impact risk requiring immediate treatment include declining demand for vape setting services, product supply disruptions, employee skill gaps, and changing government regulations. Through systematic risk assessment based on ISO 31000 framework, this research demonstrates how SMEs can optimize internal strengths such as product quality and customer servive while leveraging external opportunities like increasing vapor user trends. The study concludes that structured risk management implementation is crusial for maintaining competitiveness, enchancing operational resilience, and ensuring business sustainability in dynamic market condition. Strategic risk treatment recommendations are provided to help SMEs face business uncertainties more effectively.